2022
DOI: 10.1371/journal.pgph.0000761
|View full text |Cite
|
Sign up to set email alerts
|

Level of satisfaction and associated factors among patients attending outpatient departments of south Wollo health facilities, Ethiopia

Abstract: Background Patient satisfaction is a key metric for determining how efficient healthcare is delivered. When patients visit health care facilities, they express a clear desire for high-quality services. Inadequately meeting their anticipated needs and expectations may lead to disappointment. This study sought to investigate the level of satisfaction expressed by participants regarding services provided by outpatient departments of selected health facilities in the south Wollo zone of Ethiopia and associated pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 9 publications
0
1
0
Order By: Relevance
“…The high prevalence of satisfaction in Mildmay can be attributed to the fact that the facility offers free HCT service. The findings of the present study were higher than that of other studies that found patient satisfaction with care was relatively low among study participants at an assessment center in Mulago Hospital, Uganda (53.9%) (Kabatooro et al, 2016), a health facility in Ethiopian (64.4%) (Ayele et al, 2022) and, not any different from Calabar, Nigeria (Udonwa & Ogbonna, 2012) were level of satisfaction was reported at 57.1%. From the multi-variable modified Poisson regression model, the odds of being satisfied with HIV testing among adolescent girls and young women were 1.17 times higher among those who had primary education compared to those who were not educated, when there is no interaction between primary education and any other variable.…”
Section: Discussioncontrasting
confidence: 90%
“…The high prevalence of satisfaction in Mildmay can be attributed to the fact that the facility offers free HCT service. The findings of the present study were higher than that of other studies that found patient satisfaction with care was relatively low among study participants at an assessment center in Mulago Hospital, Uganda (53.9%) (Kabatooro et al, 2016), a health facility in Ethiopian (64.4%) (Ayele et al, 2022) and, not any different from Calabar, Nigeria (Udonwa & Ogbonna, 2012) were level of satisfaction was reported at 57.1%. From the multi-variable modified Poisson regression model, the odds of being satisfied with HIV testing among adolescent girls and young women were 1.17 times higher among those who had primary education compared to those who were not educated, when there is no interaction between primary education and any other variable.…”
Section: Discussioncontrasting
confidence: 90%
“…In a related work by Ayele et al [60], it wasreported that the result of their study revealed that overall client satisfaction was low. Furthermore, the politeness of health service providers, the convenience of the environment for asking questions, and the availability of all prescription drugs were found to have a significant relationship with level of satisfaction with the health centre.…”
Section: Discussionmentioning
confidence: 93%
“…Over the last decades, patients’ perceptions of health care have become an important indicator for measuring the quality of health care ( 10 ). Poor treatment outcomes are frequently caused by dissatisfied patients, who are more likely to skip visits, ignore treatment regimens, and leave hospitals against medical staff advice ( 11 , 12 ). Also, it can increase anxiety and irritability in patients, which results in delayed recovery time, and more beds in the hospital will be occupied by increasing the length of hospitalization and costs of treatment ( 13 ).…”
Section: Introductionmentioning
confidence: 99%